Врахування обмежень на викиди парникових газів у моделі прогнозування споживання палива на рівні країни - Maliarenko, Olena; Ivanenko, Nataliia (General Energy Institute of the National Academy of Sciences of Ukraine, 2024)
. Energy demand forecasting models have been developed at the General Energy Institute of National Academy of Sciences of Ukraine for decades. An improved normative method is known, which takes into account, the technological and structural potential of energy saving; a new complex method of forecasting the demand for energy resources, which was developed by Kulyk M.M. and improved by taking into account the fuel for conversion; life cycle models that have been extensively improved at the Institute over the past decade for various areas (nuclear energy, coal industry, oil and gas industry); the balance method developed for coal demand forecasting. These models were used in the development of Energy Strategies in Ukraine with the participation of the General Energy Institute. The actual problem is taking into account environmental restrictions in these models, which Ukraine undertook as a signatory of the Paris Agreement. Ukraine`s updated 2021 National Determined Contribution to the Paris Agreement of (NDC2), which was developed to implement environmental commitments, limits the forecast levels of greenhouse gas emissions in 2030 up to 35 % of greenhouse gas emissions in 1990. It is assumed that the same limitation can be applied to fuel consumption. The purpose of the article is to develop a mathematical model for forecasting fuel demand by taking into account the limit of greenhouse gas emissions in 2030, which allows to choose such forecast scenarios of fuel demand that, according to the total forecast volumes of greenhouse gas emissions from its consumption, meet the accepted restrictions. The article discusses the consumption of coal and oil products. Estimated volumes of coal and petroleum products consumption in case of structural and/or technological changes are calculated. An assessment of technological measures to reduce greenhouse gas emissions in various sectors of the Ukrainian economy is presented.